2013
DOI: 10.1007/s10198-013-0521-0
|View full text |Cite
|
Sign up to set email alerts
|

Health tourism on the rise? Evidence from the Balance of Payments Statistics

Abstract: The study assesses the presence and magnitude of global trends in health tourism using health-related travel (HRT) spending reported in the International Monetary Fund's Balance of Payments Statistics database. Linear regression and quantile regression are applied to estimate secular trends of the import and export of HRT based on a sample of countries from 2003 to 2009. The results show that from 2003 to 2009 the import and export of health tourism rose among countries with a high volume of such activities (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 19 publications
0
14
0
9
Order By: Relevance
“…A recent study, however, shows that the growth in health tourism in the last decade is not a universal phenomenon but rather uneven across countries with the volume of health tourism activities becoming more polarized between the high-and the low-usage countries (Loh, 2014). Consequently, a better understanding of what the determinants of health tourism are is needed.…”
Section: Global Trends In Health Tourismmentioning
confidence: 96%
“…A recent study, however, shows that the growth in health tourism in the last decade is not a universal phenomenon but rather uneven across countries with the volume of health tourism activities becoming more polarized between the high-and the low-usage countries (Loh, 2014). Consequently, a better understanding of what the determinants of health tourism are is needed.…”
Section: Global Trends In Health Tourismmentioning
confidence: 96%
“…Competition discourages accurate data, whether on numbers, market shares, or revenue. For a few countries in the Global South, medical travel ('health service exports') grew substantially from 1997 to 2010, but that growth was otherwise elusive (Lautier 2014;Loh 2014). Moreover, the objectives and outcomes of medical travel, especially in low and middle-income countries, remain 'largely anecdotal rather than statistical' (Chen and Flood 2013: 296).…”
Section: Holes In the Heart: Definitions And Datamentioning
confidence: 99%
“…However, no unequivocal research on the financial effects of health tourism was found, and the review of previous literature indicates that there are limited related studies. In other words, only a few researchers have focused on the financial effects and expenditure of health tourism (Johnson et al 2015, Loh 2014Loh 2015, Ridderstaat et al 2018, Hodžić and Paleka 2018.…”
Section: Literature Reviewmentioning
confidence: 99%